Resilience of Antibiotic Usage and Vital Signs in COVID-19 Patients: A Post-Pandemic Analysis in Pakistan - Muhammad Islam; Imtiaz Ahmed; Muhammad Shehzad; Kashif Nadeem (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2024)
COVID-19 has had a profound global impact, wreaking havoc on economies and causing a significant loss of lives. Pakistan has also faced severe consequences from the pandemic. To combat the virus, antibiotics such as Azithromycin, Ceftriaxone, Cefixime, Clarithromycin, Levofloxacin, Moxifloxacin, Meropenem, Tazobactam, Tienam, and Vancomycin have been administered to COVID-19 patients. Various vital signs such as temperature, respiratory rate, oxygen saturation, pulse rate, and blood pressure have been closely linked to the symptoms of COVID-19. This study examines the impact of antibiotic usage and vital signs on the survival and mortality of COVID-19 patients using a dataset collected from four major hospitals in Pakistan. The analytical approach includes descriptive analysis, a t-test, and a chi-square test of independence. The originality of this research lies in its comprehensive exploration of the relationship between specific antibiotics and the monitoring of vital signs in the context of COVID-19. It offers a systematic analysis of existing information to derive meaningful insights. Azithromycin emerged as the predominant antibiotic used to treat COVID-19 patients in Pakistan, with other antibiotics showing varying usage patterns. Strong, significant associations were identified between Azithromycin, Tazobactam (Tanzo), and the binary response variable (died/alive). Regarding vital signs, significant relationships were observed for patient age, systolic blood pressure, and diastolic blood pressure when compared to the response variable. This study's findings underscore the importance of Azithromycin and Tazobactam in COVID-19 treatment and highlight the role of vital signs in predicting patient outcomes.